Urgensi Nyanyian dalam Belajar Ṣarf - Zainuri Zainuri; Liya Maulidiah (An-Nuqthah, 2022)
This assistance is given to the Assunniyyah marhalah tsanawiyah students who were located in Kencong Jember. To eliminate the thought of having difficulty learning Arabic and memorizing it, the students need assistance directed at self-creativity through learning to memorize tasrifs using singing. This service research aimed to provide assistance to several students in memorizing tasrif sarf with songs. This service research used qualitative methods through documentation and observation. The results of the mentoring showed that the assisted participants were able to overcome the difficulties of memorizing nerves. Making songs can trigger awareness of how important it is to memorize Sarf.